2010
DOI: 10.3390/en4010026
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation and Distribution of Urban Energy Consumptions from Cities in China

Abstract: Abstract:With support of GIS tools and Theil index, the spatial variance of urban energy consumption in China was discussed in this paper through the parallel comparison and quantitative analysis of the 30 provincial capital cities of mainland China in 2005, in terms of scale, efficiency and structure. The indicators associated with urban energy consumption show large spatial variance across regions, possibly due to diversities of geographic features, economic development levels and local energy source availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…The results generally confirm the role of compactness (high density) in reducing energy consumption which is consistent with sustainable urban form advocates (Williams et al, 2000;Newman & Kenworthy, 1989;Howard et al, 2012;Zhang, et al, 2011). It was found that no significant association exists between energy consumption and several other aspects of urban form including building age, building façade type, and construction materials.…”
Section: Resultssupporting
confidence: 82%
“…The results generally confirm the role of compactness (high density) in reducing energy consumption which is consistent with sustainable urban form advocates (Williams et al, 2000;Newman & Kenworthy, 1989;Howard et al, 2012;Zhang, et al, 2011). It was found that no significant association exists between energy consumption and several other aspects of urban form including building age, building façade type, and construction materials.…”
Section: Resultssupporting
confidence: 82%
“…China is one of the countries with the sharpest discrepancies of population, resource distribution, and economic development among different regions in the world (Zhang et al, 2014b(Zhang et al, , 2011(Zhang et al, , 2009). This has raised the issue of how to allocate the energysaving target regionally using an equitable, reasonable, and jointly acceptable solution.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the 35 largest cities contain about 18% of the country's population and contribute to 40% of the country's energy usage and CO 2 emissions [3]. Therefore, they have become hotspots and major areas where viable solutions are being sought to tackle climate change [4][5][6]. Correspondingly, new ideas and concepts associated with development models such as the sustainable city, the eco-city, and the low-carbon city have been put forward by research groups and environmental organizations as possible solutions to the issues of energy savings and emissions reduction.…”
Section: Introductionmentioning
confidence: 99%